Association of cardiovascular-kidney-metabolic syndrome with depression and all-cause mortality: a population-based observational study - Liu, Wei; Li, Zhijuan; Ma, Pu (Frontiers in Nutrition, 2025)
BackgroundCardiovascular-Kidney-Metabolic Syndrome (CKM) is a novel multi-system disease defined by the American Heart Association (AHA). This study aims to investigate the prevalence of depression in different stages of CKM syndrome and its relationship with the risk of all-cause mortality in patients with depression.MethodsThe data used for this study were sourced from the National Health and Nutrition Examination Survey (NHANES) and the National Death Index (NDI) database, which were conducted from 2005 to 2020. CKM syndrome was classified into stages 0–4, among which stages 3–4 were defined as advanced CKM syndrome. Depression was defined according to the Patient Health Questionnaire - 9 (PHQ-9). Multivariable logistic regression and multivariable Cox regression were performed as the main analytical methods. Age-standardized prevalence analysis among four groups and Kaplan–Meier survival analysis were also carried out. Finally, a stratified analysis was conducted.ResultsA total of 15,156 participants were included in this study, with a median age of 49 years, among whom 7,608 (50%) were males. The numbers of participants in stages 0–4 of CKM were 1,360, 3,029, 8,246, 842, and 1,679, respectively. The age-standardized prevalence rates of depression in each stage were 3.40, 5.63, 7.44, 16.48, and 18.49%, respectively. In the process of logistic regression, all confounding variables were adjusted for comparison with the participants in stage 0 of CKM syndrome. It was revealed that the prevalence rates of depression in the participants of stage 1, stage 2, and stage 3 did not increase significantly (all p > 0.05), while the prevalence rate of depression in the population of stage 4 increased significantly (OR: 1.98, 95%CI: 1.40–2.82, p < 0.001). With stages 3–4 further defined as advanced CKM syndrome, the likelihood of depression in advanced CKM stages was found higher (OR: 1.47, 95%CI: 1.24–1.76, p < 0.0001). In addition, a total of 1,037 participants with depression were included for the survival analysis, and the advanced CKM stages significantly increased the risk of all-cause mortality in these patients (HR: 1.94, 95%CI: 1.29–2.93, p = 0.002). The subgroup analysis showed that the correlation between CKM syndrome and depression was stronger in the younger group (<60 years).ConclusionOur study shows that the risk of depression increases across stages 0–4 of CKM syndrome. The prevalence of depression in advanced CKM syndrome is also significantly elevated. Moreover, advanced CKM syndrome further increases the risk of all-cause mortality in patients with depression. These findings suggest that medical workers should be vigilant about the mental status of patients with advanced CKM syndrome and the risk of poor prognosis when it is complicated by depression.